Problem-solving elements in early childhood education with Bee-bot (Edma 0-6: Educación Matemática en la Infancia, 2018)
This work presents an exploratory study about problem-solving elements applied by early childhood students when solving tasks with the Bee-bot robot. These problems consist of programming the instructions that make Bee-bot move from a starting point to a final point. The aim is to observe and characterize performances in three student pairs in order to determine which heuristic resources and management processes are involved during the problem-solving process. Due to the exploratory nature of this work, we have selected two pairs from Kindergarten (5-6 years) and one pair from 1st grade (6-7 years old). The purpose is to identify divergences on the use and management of mathematical problem-solving elements previously studied and characterized in mathematics education. Moreover, the teaching sequence designed aimed at introducing programming with technological environments and developing computational thinking in early childhood students, as a way to promote problem-solving skills.
Keywords: Early Childhood Education; Problem Solving; Educational robotics; Computational Thinking